PASSING IDENTITY AND ETHNIC CULTURE IN LATVIAN EMIGRANT FAMILIES - Koroļeva, Ilze; Pranka, Maruta; Elksne, Ginta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The paper discusses the problem of preserving native Latvian language and the transfer of cultural identity in Latvian diaspora. One of the central tasks for Latvia’s diaspora policy is to support preservation of Latvian language and culture in diaspora with the aim of strengthening the Latvian identity and the sense of belonging to Latvia. Support is provided to diaspora schools for preserving Latvian language, culture and identity outside of Latvia. However, for children not to lose their Latvian language skills it is important that the language is used also in the family.This paper uses a combination of a quantitative survey and in-depth interviews with the parents of children in diaspora. The aim is to ascertain the language situation in the diaspora, explore practices and perspectives on sustaining Latvian language and ethnic culture.In the theoretical aspect, the research data is approached with reference to P. Bourdieu’s view on language skills as linguistic capital, a form of cultural capital. Parent’s attention to sustaining their heritage language in emigration is analysed in relation to children’s identity formation and family communication with family members left behind. The data confirms that parents play a big role in language acquisition and sustaining by children in emigration, and parents hold the main responsibility in the process of realizing ethnic identity as a value.